Re-escritura discursiva del terrorismo a través del cine español contemporáneo: Ocho apellidos vascos (2014) y La revolución de los ángeles (2014) - Bermúdez de Castro, Juanjo (Studia Romanica Posnaniensia, 2015)
The year 2014 saw the release of two films on the topic of terrorism from a perspective not yet adopted in Spanish fictional works: the comedy Ocho apellidos vascos, by Emilio Martínez-Lázaro, and La revolución de los ángeles, the social drama depicting the terrorist as a social activist, by Javier Silvestre, Oriol Clavell and Marc Barbena. This article explores the ways in which both approaches move away from more traditional forms of representing terrorism, such as the thriller or the emotional tribute to the victims, and to what extent the success of both films is a result of their unique perspectives on the question of terrorism.